한국 성인의 정상안에서 빛간섭단층혈관조영술 측정치의 양안 대칭성 - 박혜진(Hye Jin Park); 임형빈(Hyung Bin Lim); 이민우(Min Woo Lee); 조영준(Young Joon Jo); 김정열(Jung Yeul Kim) (Daihan angwa haghoi jabji, 2019)
목적: 한국 성인의 정상안에서 빛간섭단층혈관조영술을 이용한 측정값의 양안 대칭성을 알아보고자 하였다. 대상과 방법: 충남대학교병원 안과에 내원한 한국 성인 91명의 정상안 182안을 대상으로 의무기록을 후향적으로 분석하였다. 스펙트럼 영역 빛간섭단층혈관조영술로 얻어진 황반부의 vessel density (VD), perfusion density (PD), foveal avascular zone (FAZ)과 관련된 수치의 양안 대칭성을 확인하였다. 또한 양안 측정값의 일치도 및 연관성을 알아보기 위해 급내상관계수와 변동계수, 그리고 상관계수를 이용하여 분석하였다. 결과: FAZ area (우안: 0.30 ± 0.11 mm2, 좌안: 0.30 ± 0.10 mm2, p=0.99), FAZ perimeter (우안: 2.35 ± 0.45 mm, 좌안: 2.36 ± 0.39 mm, p=0.86), VD는 1 mm center (우안: 9.42 ± 2.75, 좌안: 9.14 ± 2.96, p=0.163), full area (우안: 19.94 ± 1.65, 좌안: 19.72 ± 1.76, p=0.285), PD는 1 mm center (우안: 0.16 ± 0.05 mm-1, 좌안: 0.16 ± 0.05 mm-1, p=0.151), full area (우안: 0.36 ± 0.03, 좌안: 0.36 ± 0.04, p=0.716)으로 양안에 유의한 차이가 없었다. 양안 측정값은 모두 급내상관계수 0.8 이상, 변동계수 10% 로 높은 일치도를 보였다. 결론: 한국 성인의 정상안에서 빛간섭단층혈관조영술로 측정한 FAZ의 크기, 황반부의 VD, PD의 수치는 양안 대칭적이었다. Purpose: To evaluate the interocular symmetry of microvascular parameters measured by optical coherence tomography angiography (OCTA) in normal eyes of Korean adults. Methods: We retrospectively reviewed the retinal microvascular structure of 91 healthy Korean subjects (182 eyes). We used OCTA to measure the area of the foveal avascular zone (FAZ), vessel density (VD), and perfusion density (PD) in both eyes. Intraclass correlation coefficients (ICCs), coefficients of variation (CVs), and Pearson correlation coefficients were calculated to evaluate the extent of agreement and correlations between binocular OCTA measurements. Results: Both eyes had similar microvascular characteristics: FAZ area (right eye: 0.31 ± 0.11 mm2, left eye: 0.30 ± 0.10 mm2, p = 0.98), FAZ perimeter (right eye: 2.35 ± 0.45 mm, left eye: 2.36 ± 0.39 mm, p = 0.86). VD 1-mm center (right eye: 9.42 ± 2.75, left eye: 9.14 ± 2.96, p = 0.163), full area (right eye: 19.94 ± 1.65, left eye: 19.72 ± 1.76, p = 0.285), and PD 1-mm center (right eye: 0.16 ± 0.05, left eye: 0.16 ± 0.05, p = 0.151), full area (right eye: 0.36 ± 0.03, left eye: 0.36 ± 0.04, p = 0.716). All ICC values were above 0.8 and all CVs below 10%. Conclusions: The microvascular structure, as represented by the VD, PD, and FAZ area measured via OCTA, was bilaterally symmetric in normal eyes of Korean adults. KCI Citation Count: 0